Analysis of Management Accounting Systems Affecting Energy Efficiency, Environmental Uncertainty and Environmental Performance of Small and Medium Enterprises - Eko Riyan Setiawan; Khairina Nur Izzaty (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
The purpose of this study was to analyze the management accounting system in influencing energy, environmental uncertainty and environmental performance in SMEs in Grobogan Regency. The population of this study is SMEs in the grobogan registered at the Grobogan Regency Cooperative and SME Office with a sample of 60 SME owners. The analytical tool used is Smart PLS 3.0. The results of this study are a positive management accounting system on energy efficiency, a positive negative management accounting system on environmental planning, a positive management accounting system supporting environmental improvement. The results of the fourth hypothesis confirm positive energy efficiency on Environmental performance. Subsequent results indicate environmental policy.